Diversidade e seleção de linhagens de Saccharomyces cerevisiae isoladas de uvas utilizadas na produção de vinhos no Vale do São Francisco, Brasil - Gomes, Camila Munique Paula Baltar Silva de Ponzzes (2010)
Wine which is being produced at São Francisco Valley is conquesting both Brazilian and International markets. However, this region does not have a typical wine produced with indigenous yeasts. The aim of this study was to select strains of Saccharomyces cerevisiae isolated from the fermented must of the Vitis vinifera L. grapes grown at São Francisco Valley in order to use them as starter culture of the fermentative process for wine preparation. From the must naturally fermented 155 S. cerevisiae and 60 non- Saccharomyces yeasts were isolated and identified. The non- Saccharomyces yeast species belonged to the genera Pichia, Rhodotorula, Candida, Wickerhamomyces and Kloeckera. The identification of the non- Saccharomyces yeasts, except for K. apis, was done by the sequencing of the D1/D2 domains of the large subunit of the rRNA gene. Amongst the 155 S. cerevisiae isolates, four molecular profiles of indigenous strains were found by using the mitochrondial DNA restriction technique. The indigenous strains and a commercial starter culture were tested in synthetic medium in order to select the strains with better fermentation performance. Two strain were selected (68 and 152), and together with the commercial strain were utilized to make wine in small scale using the grape cultivar Cabernet Sauvignon. The physicochemical analyses of the wine produced by the three strains were similar. By using the mitochrondial DNA restriction technique it was possible to observe that the strain 152 was predominant at the end of the alcohol and malolactic fermentations, whereas the strain 68 did not dominate the fermentation. The results suggest that the strain 152 could be used to produce wine at São Francisco Valley.